REGULAR Novel of comparative jurisprudence - Калюжний, Ростислав Андрійович; Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Was published scientific journal "Comparative Law". It is also a scientific and educational work, which has a dual function: comparative highlights achievements known in the field of general theory of law professionals and allows to get closer to the high-level interpretation of the nature and interaction of individual legal phenomena that operate within the legal systems of various types.